AMIR TEMUR AND THE PERIOD OF THE TEMURIDS - Teshaboyeva Nafisa Zubaydulla qizi,; Xalilova Sevinch, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:this passage explores the historical significance of Amir Temur and the  Timurid  period  and  their  role  in  shaping  political,  cultural,  and  international relations in Central Asia. It highlights Amir Temur’s leadership, his efforts to unite vast territories, and his contribution to establishing a powerful and centralized state. The article emphasizes the importance of major Timurid cities such as Samarkand, Herat,  Bukhara,  and  Shahrisabz,  which  became  centers  of  science,  culture, architecture,  and  diplomacy.The  passage  also  explains  how  Amir  Temur  used diplomacy,  trade  relations,  and  strategic  alliances  to  strengthen  international connections  with  Europe,  the  Middle  East,  and  Asia.  It  discusses  the  cultural  and scientific achievements of the Timurid period, particularly in architecture, astronomy, literature, and education, which enhanced the region’s global prestige.Furthermore, the article examines the political and economic impact of the Timurid state, including the development of trade routes, state administration, and military organization. Despite internal conflicts after Amir Temur’s death, the passage concludes that the Timurid period left a lasting legacy and continues to play a significant role in understanding Uzbekistan’s historical identity and its contribution to world civilization.